Effects of Gelatin/Chitosan and Chitosan Active Films with Rice Bran Extract for the Preservation of Fresh Pork Meat - María Cabeza de Vaca; Rosario Ramírez; Javier Rocha-Pimienta; David Tejerina; Jonathan Delgado-Adámez (Gels, 2025)
Films formulated with gelatin and chitosan (GL/CH) or chitosan (CH), without or with 0.3% and 0.5% concentrations of rice bran extract (RBE), have been developed. The migrations of rice bran extract and the antioxidant and antimicrobial properties in vitro have been assessed. The effects of the film formulations in maintaining color stability, oxidative status and microbial loads on fresh pork meat during 9 days of refrigerated storage were studied. For the films, releases of γ-oryzanol only were observed in low polarity simulant. The highest migrations and antioxidant activity were related to gelatine films, enhanced with the addition of rice bran extract. Only chitosan films showed antimicrobial activity in vitro against Escherichia coli and Listeria innocua, reaching decreases of 7.68 and 8.06 Log CFU at 72 h, respectively. Both gelatin/chitosan and chitosan films prevented the color changes in meat during storage, preventing the paleness, and chitosan films also provoked an increment of redness until 2.88 units of CIE b* at day 9. The films did not prevent either lipid or protein oxidation in meat, despite the rice bran extract inclusion, even increasing the lipid oxidations with chitosan films. However, all films helped to control the microbial counts in meat throughout all the storage, with chitosan being the most effective films, especially with the addition of RBE. Overall, gelatin/chitosan and chitosan films offer a sustainable alternative for fresh pork meat packaging.